Experimental evidence of socio-spatial intolerance between female roe deer. Issue 5 (3rd September 2018) - Maublanc, Marie-Line; Daubord, Lucie; Bideau, Éric; Gerard, Jean-François
Abstract : Female roe deer tend to live in mixed-sex groups in winter but in solitary manner on reduced home ranges in spring. This tendency is commonly related in the literature to the rearing of hiding fawns. We studied the socio-spatial relationships between six female roe deer, introduced at 1 year of age into a partly wooded 14.2-ha enclosure. Animals were monitored with GPS telemetry collars for a period of 3 years, a male being added at the end of the 2nd year. Females did not share large overlapping home ranges. In the absence of any male and offspring, they spread out in May–June (birthing season) and in July-August (rutting season). During these seasons, the size and overlap of their home ranges were minimal, while the mean distance between the arithmetic centres of their respective locations reached its maximum value and was greater than expected under the hypothesis that the females positioned their ranges independently of one another. Related females were not preferentially associated beyond 2 years of age. Moreover, the introduction of a male affected this spatial organisation only slightly. Overall, the socio-spatial organisation of female roe deer appears to be almost independent of their reproductive status, and very similar to that of males, as is the case in a number of other small-bodied ruminants.